Comparison of nutrient composition in wild caught and cultured Cirrhinus molitorella (Valenciennes, 1844) - Cui, Ke; Zhou, Falin; Ma, Zhenhua; Jiang, Shigui (Indian Journal of Fisheries, 2017)
Proximate body composition and amino acid profile of flesh of wild Cirrhinus molitorella (Valenciennes, 1844) from a reservoir and a river was compared with that of C. molitorella cultured in an aquaculture pond. The results showed the fat content to be highest in C. molitorella caught from reservoir followed by samples from river and lowest in pond cultured fishes. Protein content exhibited the opposite trend. Flesh of C. molitorella from river had optimum protein quality while flesh of fishes from reservoir had the best taste. Flesh of C. molitorella was found to be nutritionally rich and well balanced and its high glutamic acid as well as lysine content made it a superior forage fish for Siniperca chuatsi. Overall, C. molitorella flesh had a more balanced nutritional composition, but lower nutritional value than that of seven other reference fish species.